Desempeño reproductivo de vaconas Brangus a diferentes edades y pesos sometidas a protocolo de progesterona intravaginal y benzoato de estradiol - Moreira Ferrín, Jonathan Adrián (2022)
The present research was developed with the objective of evaluating the reproductive performance of Brangus cows of different ages and weights subjected to a protocol with intravaginal progesterone and estradiol benzoate. For this purpose, 100 heifers were divided into four treatments, each one with 25 heifers and each one corresponding to one experimental unit; divided into four treatments (T), as follows T1 age (20 to 22 months) and weight (220 to 320 kg); T2 age (26 to 28 months) and weight (220 to 320 kg); T3 age (20 to 22 months) and weight (325 to 430 kg); T4 age (26 to 28 months) and weight (325 to 430), a completely randomized design with 2x2 factorial arrangement was used. The results show that the heifer synchronization protocol used in T4 presents better reproductive parameters, since it obtained a better diameter of the dominant follicle when the device was removed (9.08 mm), in the presentation of estrus a value of 72% was obtained and a pregnancy percentage of 60%, with significant differences (p<0.05) compared to the other treatments. Finally, it can be established that the best age and weight for the performance of fixed-time artificial insemination in Brangus cows are found in T4 with factor A (Age 2: 26 to 28 months) and factor B (Weight 2: 325 to 430 kg), where the cows of higher age and weight present better reproductive parameters.